The Influence Word of Mouth and Location on Purchasing Decisions at MM Food Court Tabalong - Ahmad Farhani (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
With the advancement of the economy and technology, the business world is also experiencing rapid growth with the emergence of various companies striving to create products and services to meet customer needs when making purchasing decisions. The purpose of this research is to identify and analyze the influence of word of mouth and location on purchasing decisions at MM Food Court Tabalong. The research method used in this study employs a quantitative descriptive approach; the population and sample consist of 56 respondents selected through random sampling techniques. Data collection was conducted using questionnaires, and the data analysis utilized statistical tests. The results of the study indicate that word of mouth and location have an influence on purchasing decisions, with the magnitude of the influence being 28.2%, and the remaining 71.8% attributed to variables not examined in this study.